Protecting group free and scalable approach towards total synthesis of (-)-venlafaxine - Chavan, Subhash P.; Pawar, Kailash P.; Garai, Sumanta (RSC Advances, 2014)
A protecting group free asymmetric total synthesis of (-)-venlafaxine is reported. The strategy employs Sharpless epoxidation and regio-selective epoxide ring opening by an in situ generated Gilman reagent as key steps. This paper reports a 53% overall yield in 6 steps for total synthesis of (-)-venlafaxine.